Quality of Life in Pre- and Post-Treatment among Head and Neck Cancer Survivors at A Tertiary Centre, Malaysia - Ludin, Salizar M; Abdullah, Che-Azunie C; Abdullah, Kahairi (UI Scholars Hub, 2018)
Background: Treatment for head and neck cancer (HNC) may result in a variety of long term consequences that impair their health and quality of life (QoL). HNC patients often are prone to have a poor health related QoL due to significant changes in vital functions. Despite researches being done in the area cancer survivors' QoL internationally, those done locally were relatively scares and not clear. The study aim to determine and compares the pre and post treatments QoL in HNC patients. Methods: A cohort study was carried out to recruit 81 newly diagnosed HNC patients purposively; pre and six months post treatment using QoL Cancer Survivor and Questionnaire-Head &Neck 35 questionnaires. .Data was analyzed for descriptive and inferential analysis. Results: A total of 40 (50%) patients participated and the result shows that QoL of HNC patients were at medium level (6.22 ± 1.8) pre-treatment, and however reduced (4.84 ± 1.16) at 6 months post treatment), despite the symptoms or problems that occur reduced post treatment compared (1.58 ± 1.25). The Pearson coefficient correlation test result shows that QoL of HNC patients pre and post treatment were strong but negatively correlated (r = -0.447, p = 0.002). Conclusion: Understanding of QoL and affecting factors in HNC patients' QoL is very crucial as it may potentially assist in designing interventions that lessen the adverse impact of this disease process and more accurately support those in active treatment, survivors, and caregivers.